2005
DOI: 10.1253/circj.69.1514
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Atrial Fibrillation After Internal Cardioversion of Persistent Atrial Fibrillation Prognostic Importance of Electrophysiologic Parameters

Abstract: trial fibrillation (AF) is the most common cardiac arrhythmia, and its prevalence increases with age. 1 AF may cause symptoms of disability, increase the risk of thromboembolic events and is related to increased mortality. 2,3 The general treatment strategy for persistent AF (PAF) is the restoration and maintenance of sinus rhythm (SR). Whether this approach is superior to anticoagulation therapy and heart rate control remains controversial, 4,5 which increases the necessity to predict successful cardioversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…24,25) In fact, BNP levels have previously been shown to increase in the presence of AF despite the absence of heart failure. [5][6][7][8] Lee, et al 7) concluded that BNP levels were found to be significantly correlated with the left atrial volume index and tissue Doppler-derived E/E' (as an indicator of diastolic function) in patients with lone AF after adjusting for clinical and echocardiographic variables. McCullough, et al 8) showed that elevated BNP levels in patients with AF reflect chronic changes in ventricular filling dynamics and wall tension, which are independent of ejection fraction.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25) In fact, BNP levels have previously been shown to increase in the presence of AF despite the absence of heart failure. [5][6][7][8] Lee, et al 7) concluded that BNP levels were found to be significantly correlated with the left atrial volume index and tissue Doppler-derived E/E' (as an indicator of diastolic function) in patients with lone AF after adjusting for clinical and echocardiographic variables. McCullough, et al 8) showed that elevated BNP levels in patients with AF reflect chronic changes in ventricular filling dynamics and wall tension, which are independent of ejection fraction.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…[1][2][3][4] However, a recent study demonstrated that BNP levels were significantly elevated in outpatients with atrial fibrillation (AF) (median value, 131 pg/ mL) as compared to outpatients without AF (median value, 49 pg/mL; P < 0.001) despite a similar left ventricular ejection fraction (60% versus 60%, P = 0.85). [5][6][7][8] Although the pathophysiology of elevated BNP levels in AF patients has not been fully proven, this may be associated with a functional latent ventricular dysfunction such as an unfavorable hemodynamic profile or altered left ventricular filling pattern resulting from an atrial structural dysfunction. 7,8) However, the electrophysiologic consequences of the elevated BNP level in AF patients are not well known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,[12][13][14] This AF-induced shortening of atrial action potential results from downregulation of a number of ionic currents (electrical remodeling). The L-type Ca 2+ (I ca, L ) current, the transient outward current (I to ), and the ultrarapid delayed rectifier current (I Kur ) are reduced after prolonged rapid atrial pacing or AF.…”
Section: Effects Of Class III Antiarrhythmic Drugs In the Remodeled Hmentioning
confidence: 99%
“…However, atrial MAPD and ERP in patients with persistent AF show rate-dependent shortening. [12][13][14]18) Therefore, some differences may exist in the electrophysiologic effects of various class III antiarrhythmic drugs on the remodeled atrium.…”
Section: Effects Of Class III Antiarrhythmic Drugs In the Remodeled Hmentioning
confidence: 99%